2018
DOI: 10.22603/ssrr.2017-0071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of High-Intensity Zones in the Lumbar Spine According to Age and Their Correlation with Other Degenerative Findings on Magnetic Resonance Imaging

Abstract: Introduction: A high-intensity zone (HIZ) in an intervertebral disc of the lumbar spine is a high-intensity signal located in the posterior annulus fibrosus on T2-weighted magnetic resonance imaging (MRI). There is limited information on the prevalence of HIZ in the lumbar spine according to age. The aim of this cross-sectional study was to investigate the prevalence of HIZ in the lumbar spine by age and the correlation between HIZ and other degenerative findings, such as disc degeneration, disc bulging and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Series studies revealed that the prevalence of HIZ is not only increasing with aging but also closely relating to disc degeneration and low back pain in adults. 52 , 53 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Series studies revealed that the prevalence of HIZ is not only increasing with aging but also closely relating to disc degeneration and low back pain in adults. 52 , 53 …”
Section: Discussionmentioning
confidence: 99%
“…Series studies revealed that the prevalence of HIZ is not only increasing with aging but also closely relating to disc degeneration and low back pain in adults. 52,53 Modic changes are a series of degenerative changes involving the vertebral endplates and adjacent vertebral bodies. 11 Modic changes are frequently located adjacent to the degenerated disc and at the 2 lowest levels, 49 implying the potential link between Modic changes and disc degeneration.…”
Section: Hiz and Modic Changesmentioning
confidence: 99%
“…Previous studies suggest lumbar HIZs are highly associated with disc degeneration. 6 , 8 , 20 , 22 , 30 The current study analyzed the relationship between cervical HIZs (as well as HIZ subtypes) and other disc pathologies, stratified by concurrence at the same intervertebral level, and by incidence overall from C2-C7. Unexpectedly, cervical HIZs were significantly associated with lower odds of concurrent disc degeneration and disc displacement.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between HIZ lesions and clinical symptoms has been the subject to several studies [8][9][10][11][12][13] ; however, research examining the association with other degenerative processes of the spine is limited 14 . MRI-detected HIZ has been reported to be a very effective technique for screening lumbar intervertebral disc degeneration (IDD).…”
Section: Introductionmentioning
confidence: 99%